Enhancing imagined contact to reduce prejudice against people with schizophrenia - West, K; Holmes, E; Hewstone, M (2011)
Four studies investigated the effect of imagining intergroup contact on prejudice against people with schizophrenia. Experiments 1 and 2 demonstrated that a neutral imagined contact task can have negative effects, compared to a control condition, even when paired with incidental positive information (Experiment 2). Experiments 3 and 4 demonstrated, however, that an integrated positive imagined contact scenario does result in less intergroup anxiety and more positive attitudes, even toward this challenging group. Analyses of participants' descriptions of the imagined interactions in and across the first three studies confirm that positive and high quality imagined contact is important for reducing prejudice, but failing to ensure that imagined contact is positive may have deleterious consequences. We emphasize the importance of investigating the quality of the imagined contact experience, and discuss the implications for using imagined contact as a prejudice-reducing intervention. © The Author(s) 2011.